The Oxford dictionary of plays - Patterson, Michael; Oxford eBooks ([New York] : Oxford University Press, 2005)
'The Oxford Dictionary of Plays' provides information on 1000 of the most important plays of world theatre. Each entry contains information including title, author, dates of composition and first performance, genre, composition of the cast, a synopsis of the plot, and a brief commentary.
"Oxford Reference Online Premium."
Title from home page (viewed Jan. 6, 2010).
Also issued in print format.
Keywords: Drama -- Dictionaries; Electronic books